Medical records officer competency in Malaysia / Aniza Jamaluddin - Jamaluddin, Aniza (2010)
Healthcare delivery in Malaysia has grown to become a huge sector that is recognized to provide patient care in most efficient and effective way. There are rapid increases in the produced information has had dual consequences as the management of particular health information has become even more complicated. Individuals are now struggle with the huge amounts of information that comes from diverse sources. Medical record officer plays important in ensuring the effective and efficient of medical records management throughout the healthcare service and therefore, Medical Records Officer should have the competencies and skills required of medical records professionals in healthcare industry. There are insufficiency skills in managing medical records program as there is no specific comprehensive scheme in measuring Medical Records Officer’s competency that suit to Malaysia environment. In this study, the roles and responsibilities related to the delivery of Medical Records management are determined and customized based on the Malaysia environment. This study served to contribute to the development of activities supporting the competencies required for Medical Records Officer as well as the development of university curriculum in Medical Records Management. Thus, it is also created to serve as a baseline for the acquisition and development of corresponding training. Interviews instruments were used and it participated of Medical Records Officer from three private hospitals. The results of the findings were analyzed and discussed in order for the researcher to formulate the Medical Records Officer competency framework at the end of the research study